Cophylogenetic analysis of lice in the Colpocephalum complex (Phthiraptera: Amblycera). (10th November 2017) - Catanach, Therese A.; Valim, Michel P.; Weckstein, Jason D.; Johnson, Kevin P.
Abstract : The chewing louse genus Colpocephalum parasitizes nearly a dozen distantly related orders of birds. Such a broad host distribution is relatively unusual in lice. However, the monophyly of the genus Colpocephalum has never been tested using molecular characters. Using one nuclear and one mitochondrial gene, we inferred a phylogeny for 54 lice from the genus Colpocephalum and other morphologically similar genera. The resulting phylogeny demonstrates that Colpocephalum itself is not monophyletic. However, these data support the existence of a Colpocephalum complex within which several lineages are restricted to particular host orders. These lineages corresponded to previously described genera, some of which are morphologically distinct and currently considered subgenera. Maddison–Slatkin tests were performed on the resulting phylogeny and showed that host order, host family and biogeographic region had significant phylogenetic signal when mapped onto the Colpocephalum complex phylogeny. A PARAFIT analysis comparing the overall Colpocephalum complex phylogeny to a host phylogeny revealed significant congruence between host and parasite trees. We also compared the cophylogenetic history of Colpocephalum and their hosts to that of a second distantly related feather louse genus, Degeeriella, which also infests diurnal birds of prey. Using PARAFIT to identify individual host–parasite links that contributed to overall congruence, there was no evidence of correlated cophylogenetic patterns between these two louse groups, suggesting that their host distribution patterns have been shaped by different evolutionary processes.